The Role of Blue Economy On Indonesia Eco-Tourism By Empowering Local Communities: A Literature Review - Muhammad; Dimas; Irma; Vian; Refiana; Septian; Nurkholish; Annisa (PROSENAMA, 2024)
The Blue Economy presents significant opportunities for Indonesia to enhance its tourism sector while empowering local communities through sustainable practices. This framework emphasizes the responsible use of marine resources, promoting eco-tourism and empowering local communities. By encouraging community involvement in decision-making processes, the blue economy facilitates equitable distribution of tourism benefits, thereby improving livelihoods and positively impacting social dynamics. However, the successful implementation of the blue economy in Indonesia faces challenges, including climate change impacts, waste management issues, and the need for inclusive governance. To address these challenges, policies that consider the interests of all stakeholders must be developed to unlock the full potential of the blue economy. Ultimately, by prioritizing sustainability and community empowerment, Indonesia can create a resilient tourism industry that balances economic growth with environmental stewardship, paving the way for a prosperous and equitable future for its coastal communities. This study will review relevant academic articles to examine the potential of the Blue Economy in developing coastal economies on Indonesia